2015
DOI: 10.1590/1414-431x20154773
|View full text |Cite
|
Sign up to set email alerts
|

Cocos nucifera (L.) (Arecaceae): A phytochemical and pharmacological review

Abstract: Cocos nucifera (L.) (Arecaceae) is commonly called the “coconut tree” and is the most naturally widespread fruit plant on Earth. Throughout history, humans have used medicinal plants therapeutically, and minerals, plants, and animals have traditionally been the main sources of drugs. The constituents of C. nucifera have some biological effects, such as antihelminthic, anti-inflammatory, antinociceptive, antioxidant, antifungal, antimicrobial, and antitumor activities. Our objective in the present study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(161 citation statements)
references
References 56 publications
(64 reference statements)
4
108
0
20
Order By: Relevance
“…The reason that can justify such contradiction is might be due to the fatty acids contents in the VCO. It is reported that content of active compound present in the plant might vary according to the geographical area that includes soil content and seasonal variations [9]. Since the coconut used in this project are collected from a local farm in Malaysia, and the VCO used in the contradict claims were from India, the geographical difference might have influence in the active compound of VCO which in this case, the fatty acids to be different.…”
Section: Advances In Health Science Research Volumementioning
confidence: 98%
See 1 more Smart Citation
“…The reason that can justify such contradiction is might be due to the fatty acids contents in the VCO. It is reported that content of active compound present in the plant might vary according to the geographical area that includes soil content and seasonal variations [9]. Since the coconut used in this project are collected from a local farm in Malaysia, and the VCO used in the contradict claims were from India, the geographical difference might have influence in the active compound of VCO which in this case, the fatty acids to be different.…”
Section: Advances In Health Science Research Volumementioning
confidence: 98%
“…Prominent and recent studies have shown that unrefined coconut oil, Virgin Coconut oil (VCO) can be exceptionally advantageous, as it possessed antimicrobial characteristic towards a broad range of species, ranging from Mycobacterium species, Gram-positive and Gramnegative bacteria [8,9]. Differ from other common oils which are usually composed of long chain fatty acids, coconut oil and VCO are concentrated with short and medium chain fatty acids, and therefore classified as medium chain fatty acids (MCFA) [9]. Eastern scholars had outlined that, of the fatty acids present in coconut oil, lauric acid (C:12:0) is proven to be more active as antibacterial agent compared to caprylic acid (C8:0), capric acid (C10:0), and myristic acid (C14:0) [11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a tea from the husk fibers is used in Brazil against diarrhea [83] and in Haiti against amenorrhea [84], a tea from the roots would treat diarrhea and stomach pains in Papua New Guinea [85], while coconut oil would prevent hair loss and promote wound healing according to Fijan and Indonesian beliefs [86]. These actions may be associated with the presence of phenols, tannins, leucoanthocyanidins, flavonoids, triterpenes, steroids, alkaloids, triterpenes, saponins, and condensed tannins in several parts of the plant [87], as well as that of vitamin E and a number of fatty acids in coconut oil [88]. For these reasons, coconut oil is an important base ingredient of shower gels, shampoos and hair conditions, moisturizers, emollients, nourishing agents, body butters, fragrances, sunscreens, formulations to prevent drying of the skin, anti-redness agents, antiageing agents, and remedies for skin infections [89].…”
Section: Cocos Nucifera Lmentioning
confidence: 99%
“…In addition, other properties such as anti-hypertensive, cardio-protective, anti-seizure, cytotoxicity, hepatoprotective, vasodilation, nephronprotective, and anti-osteoporosis effects were also reported. Because each part of C. nucifera has different phytoconstituents, the pharmacological and biological effects of the plant vary according to the parts of the plant evaluated [7].…”
Section: Introductionmentioning
confidence: 99%